Prevention Of Stunting Through Cultural Approaches And Local Wisdom - Inriati Lewa; Erni Erawati; Yusuf Ismail (Syntax Corporation, 2022)
This study aims to explain stunting prevention efforts with a cultural approach and local wisdom. The type of research used is descriptive qualitative analysis research, namely with a field study approach (field study) with a deductive model. The results of the study show that the stunting prevention model is not only through the fulfillment of nutrition and nutrition, parenting, and environmental sanitation which are generally explained by health workers. Stunting prevention can be done through a cultural approach and local wisdom. In practice, every place or area must have a culture inherited from ancestors to care for and maintain a healthy body. This distinctive culture is the basis of people's lives to pay attention to the continuity of a healthy life. In addition to culture, there is local wisdom as a way of life in the form of activities that are important to be carried out by local communities in responding to various problems, including preventing stunting in order to achieve a maximum healthy standard of living.